Pyrethrins in Tanacetum cinerariifolium: biosynthesis, regulation, and agricultural application - Tuo Zeng; Jinjin Li; Jiawen Li; Hao Hu; Liyong Zhu; Kexin Liu; Jinxue Bai; Qijun Jiang; Caiyun Wang (Ornamental Plant Research)
Pyrethrum (Tanacetum cinerariifolium), a perennial herb within the Tanacetum genus, stands as a crucial source of natural insecticides pyrethrins which have been utilized for centuries. This study delves into the historical utilization of pyrethrum and elucidates the biosynthetic pathways of pyrethrum, uncovering the majority of genes responsible for pyrethrin production. Moreover, pyrethrum flowers and stems are rich in sesquiterpene lactones, known for their antifungal attributes, and they release (E)-β-farnesene, an aphid alarm pheromone that lures predators such as ladybirds. These discoveries emphasize pyrethrum's multifaceted chemical defense against various biotic adversaries and its viability as a companion plant in agricultural settings. Farmers have recognized and begun utilizing pyrethrum in this capacity. The paper underscores the need for further research to thoroughly comprehend and exploit pyrethrum defense strategies for sustainable farming practices, underscoring its potential in ecological and agricultural spheres.